Appendiceal Endometriosis and Carcinoid Presented as Acute Appendicitis in Pregnancy: A Rare Case Report and Review of the Literature - Panagiotis A. Dimitriadis; Ragai R. Makar; Gearoid Kingston; Ridzuan Farouk (Case Reports in Obstetrics and Gynecology)
A 22-year-old pregnant woman presented at the twenty-seventh week of gestation in the Emergency Department with acute abdominal pain and right iliac fossa tenderness. Urgent MRI was done and was suggestive of acute appendicitis. A laparoscopy was performed that confirmed an inflamed and purulent appendix that was removed. The technique used is described in detail. The histopathologic findings were those of acute appendicitis, carcinoid, and endometriosis of the appendix. We report the first case of this extremely rare triad presented in pregnancy.